2010
DOI: 10.1017/s0033291710002394
|View full text |Cite
|
Sign up to set email alerts
|

Community interest in predictive genetic testing for susceptibility to major depressive disorder in a large national sample

Abstract: Despite finding attitudes that genetic links to mental illness would increase rather than decrease stigma, we found strong community acceptance of depression risk genotyping, even though a predisposition to depression may only manifest upon exposure to stressful life events. Our results suggest that there will be a strong demand for predictive genetic testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…Although data on attitudes to genetic testing in PTSD are lacking, a few studies in samples comprised of individuals with other psychiatric disorders are available. For example, data from a large phone survey indicated that a history of psychiatric illness and a perceived vulnerability to depression were both related to increased interest in genetic testing for the risk of depression (Wilde et al, 2011). Those who endorsed statements about the benefits of genetic testing were more than three times more likely to indicate interest in receiving genetic testing for depression risk (Wilde et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although data on attitudes to genetic testing in PTSD are lacking, a few studies in samples comprised of individuals with other psychiatric disorders are available. For example, data from a large phone survey indicated that a history of psychiatric illness and a perceived vulnerability to depression were both related to increased interest in genetic testing for the risk of depression (Wilde et al, 2011). Those who endorsed statements about the benefits of genetic testing were more than three times more likely to indicate interest in receiving genetic testing for depression risk (Wilde et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, data from a large phone survey indicated that a history of psychiatric illness and a perceived vulnerability to depression were both related to increased interest in genetic testing for the risk of depression (Wilde et al, 2011). Those who endorsed statements about the benefits of genetic testing were more than three times more likely to indicate interest in receiving genetic testing for depression risk (Wilde et al, 2011). Among family members of individuals diagnosed with schizophrenia, 83% indicated interest in a test of genetic risk if it were available (DeLisi and Bertisch, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] When national polls are conducted, the focus is usually limited to a single condition, such as cancer or depression. 7,8 Additionally, more attention has been given to how individuals respond to genetic risk [9][10][11] rather than assessing their policy opinions. What is the view of the general public when it comes to policy issues in genetics and genomics?…”
mentioning
confidence: 99%